2013
DOI: 10.1002/cctc.201300028
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Biocatalytic Cannizzaro‐Type Reaction

Abstract: Blowing out of disproportion: Alcohol dehydrogenases were found to catalyze a bio‐Cannizzaro‐type reaction. The disproportionation of various aldehydes into their corresponding alcohols and carboxylic acids was achieved in a redox‐neutral process. The asymmetric variant proceeded with high stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…reported Novozyme 435 catalyzed Canizzaro reaction of substituted benzaldehydes ( Scheme ) . The reaction occurred in an aqueous medium at 30 o C and had no requirement for an external redox reagent like the single‐enzyme Canizzaro reaction with an aldehyde dehydrogenase In a self‐Canizzaro reaction, it is anticipated that an equal amount of alcohol and acid would be formed as a result of the disproportionation of the aldehyde. However, the team reported a rapid conversion of p ‐nitrobenzaldehyde to the alcohol precisely in 6 h using lipase.…”
Section: Introductionmentioning
confidence: 99%
“…reported Novozyme 435 catalyzed Canizzaro reaction of substituted benzaldehydes ( Scheme ) . The reaction occurred in an aqueous medium at 30 o C and had no requirement for an external redox reagent like the single‐enzyme Canizzaro reaction with an aldehyde dehydrogenase In a self‐Canizzaro reaction, it is anticipated that an equal amount of alcohol and acid would be formed as a result of the disproportionation of the aldehyde. However, the team reported a rapid conversion of p ‐nitrobenzaldehyde to the alcohol precisely in 6 h using lipase.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of the aldehyde occur via a gem ‐diol formed in aqueous environments. Wuensch and co‐workers have however demonstrated that when using catalytic amounts of cofactors, different ADHs can give significantly different ratios of alcohol and acids during time‐course reactions . As our reactions contained excess amounts of Sm NOX to ensure cofactor regeneration was not limiting the reactions, only NAD(P) + is available thus permitting only the gem ‐diol (aldehyde) oxidation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The thermostable ADH‐ht from Bacillus stearothermophilus , an ADH with known oxidation activity towards primary alcohols, exclusively accepted the carboxybenzyl (Cbz)‐protected amino alcohol ( 4 a ) and gave 27 % of the desired aldehyde within 2 h reaction time. Furthermore, ADH‐a from R. ruber , which was predominantly reported for the oxidation of secondary alcohols with few exceptions, such as 2‐phenylethanol ( 1 a ), showed no activity towards our model substrates . More promising results were obtained by applying AlkJ, an ADH from Pseudomonas putida , which was known for the oxidation of aliphatic alcohols.…”
Section: Resultsmentioning
confidence: 99%